Beyond the State: Evaluating the Impact of Women’s Peace Networks in Pakistan–India Track-II Engagements - Ayesha, Noor E; Ghani , Anfal; Khan, Azhar Shahbaz (ACADEMIA International Journal for Social Sciences, 2025)
Since traditional state-centric (Track-I) diplomacy Consistently fails to resolve long-standing territorial disputes and nuclear tensions, the ongoing animosity between India and Pakistan continues to be a major obstacle to South Asian stability. The underused potential of civil society is the analytical emphasis of this study, which focuses on the effects of women-led Track-II diplomacy. The study, which is based on feminist international relations theory, questions traditional, male-dominated security narratives by emphasizing how women put social justice, empathy, and human security ahead of military supremacy. The study assesses how these networks preserve communication amid political crises and foster informal cross-border trust using a qualitative secondary analysis of key academic publications from 2010 to 2025. Important conclusions show that women’s networks promote peace both directly through trust-building and local mediations and indirectly by humanizing the "enemy" and reframing peace as an issue of daily safety rather than merely territorial control. Significant operational limitations are identified by the research, nevertheless, such as reliance on erratic foreign finance, a lack of institutional recognition, and systemic gender inequality that confines women to advisory rather than decision-making roles. The study concludes that in order to meet the strategic requirement of the Women, Peace, and Security (WPS) agenda, women’s roles must be institutionalized and included into official policy frameworks.